ANALISIS BIBLIOMETRIK DALAM PERMAINAN UNTUK MENGEMBANGKAN KOGNITIF ANAK USIA DINI USIA 5-6 TAHUN - Hamel, Arin Auliani; Gunawan, Erlita; Hasanah, Iklimatul; Shafira, Nadia; Pertiwi, Sarah Dian; Rahima, Qhaysah Fara; Widjayatri, RR. Deni (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2023)
Every child has different cognitive development. This research aims to find out games that can develop the cognitive abilities of young children aged 5-6 years. This research uses a qualitative approach, the Systematic Literature Review (SLR) method and bibliometric analysis. The data source comes from Google Scholar using the year range 2018-2023, Harzing's Publish or Perish (Pop) and VOSviewer. The research results show that: the cognitive aspects of children aged 5-6 years can develop through play; obtained 4 clusters consisting of 4 colors, namely red, blue, green and yellow; fruit counting board games, letter cards, congklak and puzzles are in the very good category. The implication of this research is that playing is very crucial in children's lives, without realizing it, playing can develop one aspect of children's cognitive development.